Perceived controllability of group membership does not moderate individuating information effects in implicit person perception - Rubinstein, Rachel S.; Jussim, Lee; Mangracina, Brandon; Shaw, K. Mackenzie; Yanovsky, Sonia; Bennett, Samuel (Frontiers in Psychology, 2024)
Although the effects of counterstereotypic individuating information (i.e., information specific to individual members of stereotyped groups that disconfirms the group stereotype) on biases in explicit person perception are well-established, research shows mixed effects of such information on implicit person perception. The present research tested the overarching hypothesis that, when social group membership is perceived to be under an individual's control, diagnostic individuating information would have lesser effects on implicit person perception than it would when social group membership is perceived not to be under an individual's control. This hypothesis was tested in the domain of implicit attitudinal and stereotype-relevant judgments of individuals who belonged to existing social groups and individuals who belonged to novel social groups. We found that individuating information consistently shifted scores on implicit measures among targets belonging to existing social groups, but not in a theoretically predicted direction among targets belonging to novel social groups. Controllability of group membership did not moderate such effects. Results of implicit and explicit measures were mostly consistent when targets belonged to existing social groups, but mostly inconsistent when targets belonged to novel social groups.